Fatigue Life Prediction of Titanium Alloy for Block Loading Using The Hybrid Approach of Critical Plane and Continuum Damage Mechanics - M. M., Rahman; Kamal, M. (Universiti Malaysia Pahang, 2017)
The present study is related to the performance analysis of the newly proposed fatigue estimation model for titanium alloy BT9 against block loading. Lately, research efforts have been concentrated on developing the capability to handle complex multiaxial loading conditions for fatigue estimation. The current study is focused on testing the proposed hybrid approach involving the critical plane and continuum damage mechanics. The calibration of the proposed model is done by determining the model coefficients by using a genetic algorithm. Experimental fatigue lives for titanium alloy BT9 with block loading consisting of axial, torsion and out-of-phase axial–torsion loading segments are considered to analyse the accuracy of the proposed model. The proposed model is validated by using finite element analysis to estimate fatigue life for titanium alloy BT9. Simplifications were assumed to handle the block loads, and axial, torsion and out-ofphase loading conditions were used for calibration. The estimated fatigue life results show good agreement with published results for block loads.